1996
DOI: 10.1007/bf02507103
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD4 and CD8 in serum from patients with localized scleroderma

Abstract: Localized scleroderma has been shown to be accompanied by various immunologic abnormalities. To obtain functional information on activated CD4+ or CD8+ T cells, we studied the levels of soluble CD4 (sCD4) and soluble CD8 (sCD8) in serum from patients with localized scleroderma. Serum samples were examined by enzyme-linked immunosorbent assay. The samples were obtained from 49 patients in the following three subgroups: 15 patients with generalized morphea, 22 with linear scleroderma, and 12 with morphea. The le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 33 publications
0
7
0
3
Order By: Relevance
“…Serum antinuclear antibodies, most of them with a homogenous pattern, have been detected in 20% to 80% of LS patients . Moreover, active childhood LS might be associated with antihistone antibodies, hypergammaglobulinemia, and eosinophilia . In patients with linear LS of the extremities with concomitant joint involvement, increased levels of rheumatoid factor may be present, and do sometimes correlate with the clinical degree of arthritis activity .…”
Section: Serologic Featuresmentioning
confidence: 99%
“…Serum antinuclear antibodies, most of them with a homogenous pattern, have been detected in 20% to 80% of LS patients . Moreover, active childhood LS might be associated with antihistone antibodies, hypergammaglobulinemia, and eosinophilia . In patients with linear LS of the extremities with concomitant joint involvement, increased levels of rheumatoid factor may be present, and do sometimes correlate with the clinical degree of arthritis activity .…”
Section: Serologic Featuresmentioning
confidence: 99%
“…no reported studies on VEGF in morphoea, although an overall increase in levels in systemic sclerosis has been reported. 22 Sato et al 23 reviewed 49 patients with morphoea and found that serum CD4+ and CD8+ cells were significantly increased in these patients. Although our patient sample was small, our study showed a reduction in tissue levels of CD3+ and CD4+ cells following PUVA, which occurred in parallel with clinical improvement.…”
Section: Patient Nomentioning
confidence: 99%
“…Various immunologic phenoma and abnormalities such as antinuclear antibodies, antihistone and anti-single-stranded DNA antibodies, eosinophilia, hypergammaglobulinemia, and rheumatoid factor have been detected in up to 80% of patients with severe generalized or linear LS, and a correlation with the clinical activity of disease has been hypothesized. 23 Elevated levels of IgG and IgM have been reported in up to 50% of patients with severe LS. In this context, Falanga et al 24 25 Because no significant change in PIIINP was observed with therapy in 2 recent trials, we refrained from determination of PIIINP in our patients.…”
Section: Commentmentioning
confidence: 99%